Seasonal Variations of Water Quality in Bangpakong River and Nearby Canals at Banpho District - Teerada Bubphamala; Lukkhana Benjawan; Warounsak Liamlaem (Agriculture and Natural Resources, 2010)
The substantial growth in the population and industries of Banpho district, Chachoengsao recently drove the community to express concern over the health of the Bangpakong River and canals in the vicinity. The water quality of the River and canals in Banpho district was monitored monthly from November 2006 to July 2008, covering the dry season (November-April) and the wet season (May-October). The collected water samples were analyzed for pH, temperature, salinity, conductivity, turbidity, dissolved oxygen (DO) biochemical oxygen demand (BOD), nitrate-N and total and fecal coliform bacteria. The heavy metals in the water samples, Hg, Pb, Cd, Cr6+, and Mn, were determined as well. It was found that the BOD, total and fecal coliform bacteria levels were significantly higher than the standard limits for surface water quality. The levels of Pb, Hg, Cd and Mn were occasionally at higher levels than the standard limits. Among such metals, Pb and Cd were the most critical, since their highest levels were more than 15 times higher than the limits. The severity of the pollution seemed to be higher in the dry season than in the wet. Similarly, high salinity was typically found in the dry season. Furthermore, the highest amounts of the contaminants were generally found in March and April.